Water hammer analysis in a water distribution system - John Twyman (Ingeniería del Agua, 2017)
The solution to water hammer in a water distribution system (WDS) is shown by applying three hybrid methods (HM) based on the Box’s scheme, McCormack's method and Diffusive Scheme. Each HM formulation in conjunction with their relative advantages and disadvantages are reviewed. The analyzed WDS has pipes with different lengths, diameters and wave speeds, being the Courant number different in each pipe according to the adopted discretization. The HM results are compared with the results obtained by the Method of Characteristics (MOC). In reviewing the numerical attenuation, second order schemes based on Box and McCormack are more conservative from a numerical point of view, being recommendable their application in the analysis of water hammer in water distribution systems.